(untitled) (Research, Society and Development, 2020)
The article aims to highlight the policies adopted for the provision of professional education in Brazil and the influence exerted by international organizations in the context from the 1990s onwards. Methodologically, the research is inspired by the dialectic perspective, the qualitative approach and exploratory research. . The research instruments developed were a bibliographic review on the concepts pointed out by the theorization of the field of professional education (Frigotto, 1989; Ferretti, 2018; Germano, 2002; Moura, 2014; Tavares 2005; 2015) and documentary research through the study of norms (Federal Decrees 2.208 / 1997 and 5.154 / 2004) that regulate professional education in Brazil. Among the results, we emphasize that international organizations act as institutions that announce the philosophical, material and technical horizons of educational policy, configuring conservative policies. Furthermore, we argue that hegemonic capitalist thinking impacts on professional education through minimal and reductionist curricula, essentially committed to the acquisition of technical and unilateral skills for the working class, detached from the concept of integrated high school and transformative education.